2016
DOI: 10.1186/s12935-016-0300-y
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss reduces basal-like breast cancer through kinome reprogramming

Abstract: BackgroundObesity is associated with an aggressive subtype of breast cancer called basal-like breast cancer (BBC). BBC has no targeted therapies, making the need for mechanistic insight urgent. Reducing adiposity in adulthood can lower incidence of BBC in humans. Thus, this study investigated whether a dietary intervention to reduce adiposity prior to tumor onset would reverse HFD-induced BBC.MethodsAdult C3(1)-Tag mice were fed a low or high fat diet (LFD, HFD), and an obese group initially exposed to HFD was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 76 publications
0
19
0
Order By: Relevance
“…They showed that obese mice display the greatest TNBC aggression compared to tumors in lean mice with early onset (reduced latency) or increased progression and activation of certain kinases and oncogenic signaling cascades in an obesity-specific manner. [112][113][114][115][116] Formerly, obese mice that lost weight through diet alteration display reversal of that obesity-driven progression to lean levels in this spontaneous GEMM of basal-like TNBC, 113,116 as well as ongoing studies using orthotopically transplanted syngenetic models (data not shown).…”
Section: Tnbcs Also Disproportionately Affect African American Andmentioning
confidence: 88%
See 1 more Smart Citation
“…They showed that obese mice display the greatest TNBC aggression compared to tumors in lean mice with early onset (reduced latency) or increased progression and activation of certain kinases and oncogenic signaling cascades in an obesity-specific manner. [112][113][114][115][116] Formerly, obese mice that lost weight through diet alteration display reversal of that obesity-driven progression to lean levels in this spontaneous GEMM of basal-like TNBC, 113,116 as well as ongoing studies using orthotopically transplanted syngenetic models (data not shown).…”
Section: Tnbcs Also Disproportionately Affect African American Andmentioning
confidence: 88%
“…As the role of obesity in TNBC is established in epidemiologic studies 11,[140][141][142][143][144] and experimental findings are formed from our laboratory and others, 79,99,[112][113][114][115][116][134][135][136][137][138][139] it is essential to identify novel underlying mechanisms associated with obesity, weight gain, or weight loss that impact TNBC outcomes. Inflammation associated with obesity is one well-studied consequence that influences risk, tumor outcomes, and therapeutic efficacy.…”
Section: B Ile Acid S I G Naling In K E Y Immune Cell Smentioning
confidence: 99%
“…Our lab has demonstrated that inhibition of the HGF receptor, cMET, via the small molecule kinase inhibitor crizotinib significantly reduced tumor burden and tumor vascularity in both lean and obese C3(1)-TAg mice (74). Reversal of high fat diet-induced elevation of HGF/cMET expression in both normal mammary gland and tumors was also observed with weight loss, which significantly blunted the effects of obesity on both pre-neoplastic lesion formation (316) and tumor progression (377) (Fig. 16).…”
Section: Microenvironmental Links Between Adipose Tissue and Cancermentioning
confidence: 81%
“…These interventions could effectively prevent atypical ductal hyperplasia and ductal carcinoma in situ to the points observed in healthy mice. In the same study, the weight loss caused decreased activity of several kinases, which, in turn, caused abrogation of the MAPK pathway, which is related to tumor proliferation ( 115 ). Another study set out to explore this connection, studying breast cancer cells with overexpression of the HER-2 protein treated with trastuzumab, particularly regarding its ADCC mechanism, that is, the antibody-dependent cellular cytotoxicity.…”
Section: Introductionmentioning
confidence: 95%